Defects in Glycosylation Impair Satellite Stem Cell Function and Niche Composition in the Muscles of the Dystrophic Largemyd Mouse123. (20th September 2012) - Ross, Jacob; Benn, Abigail; Jonuschies, Jacqueline; Boldrin, Luisa; Muntoni, Francesco; Hewitt, Jane E.; Brown, Susan C.; Morgan, Jennifer E.
Abstract: The dystrophin‐associated glycoprotein complex (DGC) is found at the muscle fiber sarcolemma and forms an essential structural link between the basal lamina and internal cytoskeleton. In a set of muscular dystrophies known as the dystroglycanopathies, hypoglycosylation of the DGC component α‐dystroglycan results in reduced binding to basal lamina components, a loss in structural stability, and repeated cycles of muscle fiber degeneration and regeneration. The satellite cells are the key stem cells responsible for muscle repair and reside between the basal lamina and sarcolemma. In this study, we aimed to determine whether pathological changes associated with the dystroglycanopathies affect satellite cell function. In the Large myd mouse dystroglycanopathy model, satellite cells are present in significantly greater numbers but display reduced proliferation on their native muscle fibers in vitro, compared with wild type. However, when removed from their fiber, proliferation in culture is restored to that of wild type. Immunohistochemical analysis of Large myd muscle reveals alterations to the basal lamina and interstitium, including marked disorganization of laminin, upregulation of fibronectin and collagens. Proliferation and differentiation of wild‐type satellite cells is impaired when cultured on substrates such as collagen and fibronectin, compared with laminins. When engrafted into irradiated tibialis anterior muscles of mdx ‐nude mice, wild‐type satellite cells expanded on laminin contribute significantly more to muscle regeneration than those expanded on fibronectin. These results suggest that defects in α‐dystroglycan glycosylation are associated with an alteration in the satellite cell niche, and that regenerative potential in the dystroglycanopathies may be perturbed. STEM Cells 2012;30:2330–2341